The Influence Of Financial Institutions, Govermant, and Digital Technology in The Msme - khatik, Nur; Santosa, R.Ery Wibowo Agung (Department of Accounting-Faculty of Economic and Business (FEB), 2023)
AbstractThe purpose of this study was to find out how the influence of financial institutions, cooperative and SME cooperative services, and digital technology on increasing MSME businesses in Kendal Regency, the method used was the data analysis method with a questionnaire using a Likert scale 5 Multiple Linear Regression approach and the help of IBM SPSS software version 25. The results of this study indicate that financial institutions have a significant effect on MSME business development, trade and SME cooperative services have a significant effect on MSME business development, and digital technology has no effect on MSME business development in Kendal Regency Keywords: Financial Institutions, Cooperative and SME Trade Office, Digital Technology, Increasing MSME business